CFTR mutations causing congenital unilateral absence of the vas deferens (CUAVD) and congenital absence of the uterus (CAU) in a consanguineous family - Mahdieh Daliri Ghouchanatigh; Ranjha Khan; Majid Mojarrad; Uzma Hameed; Muhammad Zubair; Ahmed Waqas; Mohsen Jalali; Mahmoudreza Kalantari; Ali Shamsa; Huan Zhang; Qing-Hua Shi (Asian Journal of Andrology, 2022)
Cystic fibrosis (CF) is one of the most common recessive genetic diseases, with a wide spectrum of phenotypes, ranging from infertility to severe pulmonary disease. Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene are considered the main genetic cause for CF. In this study, we recruited a consanguineous Iranian pedigree with four male patients diagnosed with congenital unilateral absence of the vas deferens (CUAVD), and one female patient diagnosed with congenital absence of the uterus (CAU). Testicular biopsy of one patient was performed, and hematoxylin and eosin (H and E) staining of testis sections displayed the presence of germ cell types ranging from spermatogonia to mature spermatids, indicating obstructive azoospermia. To explore the underlying genetic factor in this familial disorder, we therefore performed whole-exome sequencing (WES) on all available family members. WES data filtration and CFTR haplotype analysis identified compound heterozygous mutations in CFTR among four patients (two CUAVD patients carried p.H949Y and p.L997F, and one CUAVD and the female CAU patient carried p.H949Y and p.I148T). All these mutations were predicted to be deleterious by at least half of the prediction software programs and were confirmed by Sanger sequencing. Our study reported that CFTR compound heterozygous mutations in a consanguineous Iranian family cause infertility in both sexes.